Evaluasi kemampuan literasi informasi pemustaka perpustakaan STAIN Curup menggunakan standar yang dikembangkan ACRL - Rhoni Rodin (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2016)
This study aims to identify and evaluate user ability of information literacy STAIN Curup’s Library,by applying the model Information Literacy Competency Standards developed by Association of Collegeand Research Libraries (ACRL). This type of research is analytical descriptive. The population inthis study are all users of STAIN Curup’s Library from semester I, III, V, VII, IX, the number ofusers are 2760. The sampling taken with Accidental sampling technique. Data collection techniquesusing questionnaires, interviews and documentation. Mechanical processing of data by the datachecking (Editing), give the code (Coding) and data preparation (Tabulation). While the techniqueof data analysis using descriptive analysis. The results of this research generally shows that 59% ofrespondents always include the author’s name and the source on any citations in their work. Thisshows that users are already have the ability to understanding the problems of economics, law andsocial associated with use of information legally and by ethics. Furthermore, 41% of respondentsalways formulate steps when going to search information. It shows most users are formulate the firstthings that will look for the information. Then 52% of respondents always use strategies in searchof information. From these results, it can be concluded that most users are have good informationliteracy skills in finding the information they need.